The Effectiveness of Tidy Notes Application in Writing Narrative Text at Fourth Semester of Universitas Bhinneka PGRI Tulungagung - Muaffaq, Aufal; Rakhmawati, Ika (Yayasan Pendidikan Tanggui Baimbaian, 2024)
This study discusses the effectiveness of the Tidy Notes Application in writing students' narrative texts. The purpose of this study was to determine the method of the Tidy Notes Application in writing students' narrative texts. This study uses quantitative research. The researcher used a pre-experimental design research design. The data collection methods used were pretest, treatment, and posttest. The subjects of this study were fourth-semester students at Bhinneka PGRI University Tullungagung. The average posttest was higher than the pretest, which was 90.00> 67.00, and its significance was 0.000 <0.05. The conclusion is that the